Business as Usual in Unusual Times: An explorative study of Norwegian child welfare workers’ experiences during the COVID-19 pandemic - Krane, Vibeke; Ausland, Liv Hanson; Andvig, Ellen; Klevan, Trude (Journal of Comparative Social Work, 2021)
Background: The COVID-19 pandemic has severely affected the daily lives and well-being of children and families. During the lockdown of Norway in spring 2020, many families were socially isolated and left with little support from their networks. Children and young people had limited contact with teachers, peers and other positive social contacts. The lockdown also affected the daily running of the Norwegian child welfare services (CWS), which are obliged to provide help and support to children at risk and their families. Aim: The aim of this study was to explore how leaders and staff in the CWS balanced their two-part mandate to protect children from harm, and to provide support and care during the first lockdown in Norway. Design and method: The study has a qualitative approach with a descriptive and explorative design. Thirty-six CWS workers and nine leaders participated. Focus groups, dyadic and individual qualitative interviews were used for data collection. The data were analysed with a thematic analysis. Findings: 1) ‘Running the services during a pandemic’ deals with the practical organization of staff and child welfare cases, and 2) ‘The quality of child welfare work during lockdown’ describes qualitative aspects of the child welfare work. Conclusions: The study revealed the prioritization of acute cases and a reduction in CWS contact with children and families. CWS staff worried about whether at-risk children were receiving the help they were entitled to. The study shows how the crisis led to innovative approaches and teleworking solutions. The CWS had to decide how to organize and run the services in a way that ensured both acute assessments and the long-term aspects of the CWS mandate. Considering the strain the long-term pandemic has placed on children at risk, the further organization and running of the CWS is of great importance.